Assessment of integrated process based on autohydrolysis and robust delignification process for enzymatic saccharification of bamboo. (November 2017) - Chen, Tian-Ying; Wen, Jia-Long; Wang, Bing; Wang, Han-Min; Liu, Chuan-Fu; Sun, Run-Cang
Graphical abstract: Highlights: The bamboo was successfully deconstructed using a two-step integrated process. The changes of lignin structures during autohydrolysis were deeply investigated. The enzymatic hydrolysis of the delignified substrates was observably enhanced. The structural characteristics of the lignin obtained were elaborately clarified. The process for obtaining XOS, lignin and glucose from bamboo was presented. Abstract: In this study, bamboo ( Phyllostachys pubescens ) was successfully deconstructed using an integrated process (autohydrolysis and subsequent delignification). Xylooligosaccharides, high-purity lignin, and digestible substrates for producing glucose can be consecutively collected during the integrated process. The structural change and fate of lignin during autohydrolysis process was deeply investigated. Additionally, the structural characteristics and active functional groups of the lignin fractions obtained by these delignification processes were thoroughly investigated by NMR (2D-HSQC and 31 P NMR) and GPC techniques. The chemical compositions (S, G, and H) and major linkages (β- O -4, β-β, β-5, etc.) were thoroughly assigned and the frequencies of the major lignin linkages were quantitatively compared. Considering the structural characteristics and molecular weights of the lignin as well as enzymatic saccharification ratio of the substrate, the combination of autohydrolysis and organic base-catalyzed ethanol pretreatment was deemed as a promising biorefinery mode in the future based on bamboo feedstock.